Cross‐Cultural Comparison of Nonverbal Cues in Emoticons on Twitter: Evidence from Big Data Analysis. (19th March 2014) - Park, Jaram; Baek, Young Min; Cha, Meeyoung
Abstract Relying on Gudykunst's cultural variability in communication (CVC) framework and culture‐specific facial expressions of emotion, we examined how people's use of emoticons varies cross‐culturally. By merging emoticon usage patterns on Twitter with Hofstede's national culture scores and national indicators across 78 countries, this study found that people within individualistic cultures favor horizontal and mouth‐oriented emoticons like :), while those within collectivistic cultures favor vertical and eye‐oriented emoticons like ^_^. Our study serves to demonstrate how recent big data‐driven approaches can be used to test research hypotheses in cross‐cultural communication effectively from the methodological triangulation perspective. Implications and limitations regarding the findings of this study are also discussed.